Rheological analysis of irradiated crosslinkable and scissionable polymers used for medical devices under different radiation conditions. (March 2018) - Satti, A.J.; Ressia, J.A.; Cerrada, M.L.; Andreucetti, N.A.; Vallés, E.M.
Abstract: The effects on different synthetic polymers of distinct types of radiation, gamma rays and electron beam, under different atmospheres are followed by changes in their viscoelastic behavior. Taking into account the two main radioinduced reactions, crosslinking and scissioning of polymeric chains, liquid polydimethylsiloxane has been used as example of crosslinkable polymer and semi crystalline polypropylene as example of scissionable polymer. Propylene − 1-hexene copolymers have been also evaluated, and the effects of both reactions were clearly noticed. Accordingly, samples of those aforementioned polymers have been irradiated with 60 Co gamma irradiation in air and under vacuum, and also with electron beam, at similar doses. Sinusoidal dynamic oscillation experiments showed a significant increase in branching and crosslinking reactions when specimens are irradiated under vacuum, while scissioning reactions were observed for the different polymers when irradiation takes place under air with either gamma irradiation or electron beam. Highlights: Analysis of gamma and EB irradiated scissionable iPP and crosslinkable PDMS. Similar decrease of viscoelasticity of all irradiated samples with air gamma and EB. Crosslinking in vacuum irradiation for PDMS, and sort of in iPP copolymers. Amorphous iPP tend to branching when irradiated, specially, under vacuum.